Synthesis, Spectroscopic Characterization, and Biological Evaluation of Some Transition Metal Complexes from C16H19N3O3S Ligand - Sura K. Ibrahim (Journal of Global Pharma Technology, 2016)
A first series of transition metal complexes were synthesized from the ligand Methyl -6- [2-(benzyl ideneamino) -2- (4-hydroxyphenyl) acetamido]-2, 2-dimethyl -5-oxo-1-thia 4-azabicyclo [3.2.0] heptane-3-carboxylate with appropriative metal salts. The complexes were characterized by spectral methods such as FTIR, Uv-Visible, and Atomic absorption as well as some physical properties, molar conductivity and magnetic moment measurements. The results showed that the proposed structures of these complexes are Octahedral, except Co II is a tetrahedral geometry. The biological activities of these complexes were studied using two types of bacteria (Staphylococcus aures, Echerchia coli) in addition to Candical albicans c. albicans that gave results a good activity than the free ligand.